KAJIAN ASPEK FINANSIAL USAHA IKAN HIAS AIR TAWAR - Hasyim, Ema Agustien; Komalasari, Dian (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2010)
Ornamental fish business is one of the rapidly growing agribusiness and provide benefits, but this business requires a good and proper handling. This business is influenced by trends and consumer tastes, then the employer must respond quickly and meet market demand. Case study method is a method used to examine the sensitivity analysis financially and Rainbow ornamental fish business. Advantages rselama five years amounted to USD 224463000, and the ornamental fish business financially feasible type of rainbow is developed, then the sensitivity analysis terhdapat discount faktor 6; 10; and 18% showed sensitivity to the selling price of fish